A Roadmap to Problematic Pornography Use: Research, Assessment, and Treatment - Dinçer, Eren Murat; Durmuş, Hasan; Demirgül, Süleyman Agah; Kavla, Yasin; Kitapçıoğlu, Süreyyanur; Aktürk, İlker; Bozdemir, Tuğba; Sandıkçı, Tuncay; Büyükçorak, Mehmet; Barış, Feride Yüksel (Addicta: The Turkish Journal on Addictions, 2025)
Problematic pornography use has gained increasing scholarly and clinical attention over the past decade. Despite this, definitions remain contested, classification models are inconsistent, and measurement approaches vary, creating barriers for cumulative knowledge and evidence-based practice. This review provides an overview of the conceptual, methodological, and clinical landscape of problematic pornography use. The goal is to guide researchers and practitioners by summarizing current knowledge, identifying research gaps, and highlighting future directions. A narrative review of the literature was conducted, synthesizing theoretical models, epidemiological findings, measurement tools, identified risk and protective factors, and available intervention approaches. Special attention was given to cultural variation, usage characteristics, and the role of moral incongruence. Findings indicate that problematic pornography use is situated at the intersection of behavioral addictions, impulse-control difficulties, and compulsive tendencies, with no consensus on a unifying framework. Prevalence estimates vary widely due to sampling bias and definitional inconsistencies. Risk factors include impulsivity, insecure attachment, and early exposure, while protective factors such as family support and ethical disapproval may buffer risk. Excessive pornography use has been linked to psychological distress, relationship difficulties, and aggressive sexual attitudes, though associations are moderated by contextual variables. Measurement remains inconsistent, with few tools aligned with diagnostic criteria. Interventions such as cognitive behavioral therapy, acceptance and commitment therapy, mindfulness, and pharmacological options show promise, but evidence is limited by small samples and short follow-ups. Future research should prioritize standardized definitions, culturally adapted measurement, inclusion of content-type variables, and methodologically rigorous longitudinal designs. Clinical efforts must expand to diverse populations and relational contexts, moving the field toward an empirically grounded and ethically responsible science of problematic pornography use
Keywords: Addictions to technology; pornography research; Problematic pornography use